2010
DOI: 10.1016/j.sleep.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Who gets the best sleep? Ethnic and socioeconomic factors related to sleep complaints

Abstract: Objectives-Lower socioeconomic status is associated with short or long sleep duration and sleep disturbance (e.g., sleep apnea), which are all related to increased mortality risk. General sleep complaints, however, which may better approximate symptoms as they are experienced, have not been examined in a large population sample.Methods-Sample consisted of n=159,856 participants from the Behavioral Risk Factor Surveillance System, representing 36 states/regions across the US. Sleep complaints were measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
312
12
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(383 citation statements)
references
References 34 publications
50
312
12
9
Order By: Relevance
“…The number of children in the household appears largely unexplored in previous research [19][20][21], which was examined dichotomously [12] or restricted to very young children [15]. Notably, we found that the likelihood of frequent insufficient sleep followed a linear trend with number of children for married and previously married men and women.…”
Section: Discussionmentioning
confidence: 53%
“…The number of children in the household appears largely unexplored in previous research [19][20][21], which was examined dichotomously [12] or restricted to very young children [15]. Notably, we found that the likelihood of frequent insufficient sleep followed a linear trend with number of children for married and previously married men and women.…”
Section: Discussionmentioning
confidence: 53%
“…The finding that outright sleep quality complaints did not differentiate the groups was not surprising, as recent large-scale epidemiological studies have found that general sleep complaints are not differentially reported in black and white respondents, 16 though other studies have found differences in sleep complaints. 9 A lack of difference in complaints may belie problems, as black individuals are at greater risk of disturbed sleep (eg, symptoms of sleep apnea) when measured in the laboratory, 32 suggesting a discrepancy between reported symptoms and those observed.…”
Section: Discussionmentioning
confidence: 84%
“…Epidemiological data suggest that sleep difficulties are more prevalent among individuals with a low income, low educational attainment, and those unemployed (Ford and Kamerow 1989;Grandner et al 2010;Ohayon 2002). They are also more prevalent in separated/divorced and widowed individuals as compared to married couples (Ford and Kamerow 1989;Grandner et al 2010;Hale 2005), and in women experiencing less marital satisfaction (Troxel et al 2009).…”
Section: Candidate Nonshared Environmental Influences On Sleepmentioning
confidence: 99%
“…They are also more prevalent in separated/divorced and widowed individuals as compared to married couples (Ford and Kamerow 1989;Grandner et al 2010;Hale 2005), and in women experiencing less marital satisfaction (Troxel et al 2009). …”
Section: Candidate Nonshared Environmental Influences On Sleepmentioning
confidence: 99%